Unveiling spin-glass transition and antiferromagnetic order by μSR studies in spin-chain Sm2BaNiO5. (20th February 2019) - Indra, A; Dey, K; Bhattacharyya, A; Berlie, A; Giri, S
Abstract: We report the zero-field and longitudinal field muon spin relaxation studies in a spin-chain compound Sm2 BaNiO5 . Two magnetic transitions, that have not been previously detected by the heat capacity and magnetization measurements, are confirmed at 46 and 9 K. The antiferromagnetic order is suggested at 46 K. Analysis of the muon spin polarization unveils the spin-glass transition at 9 K. Time-field scaling relation of the muon spin polarization verifies the spin–spin autocorrelation function following the cut-off power law, which is approximated by the Ogielski form, as employed numerically for characterizing the spin-glasses.